Use of the Arabin pessary in women at high risk for preterm birth: long-term experience at a single tertiary center in Malaysia - Rahana Abd Rahman; Ixora Kamisan Atan; Anizah Ali; Aida Mohd Kalok; Nor Azlin Mohamed Ismail; Zaleha Abdullah Mahdy; Shuhaila Ahmad (BMC, 2021)
Abstract Background Spontaneous preterm birth is a global issue that contributed to perinatal morbidities and mortalities worldwide. The study aimed to describe the experience at UKM Medical Center in managing women at high risk for spontaneous preterm birth using the Arabin pessary. Methods This is a retrospective observational study involving 58 pregnancies from 1st January 2013 to 31st December 2019. Inclusion criteria were previous mid-trimester miscarriage and/or preterm birth, previous cervical surgery or short cervical length on routine sonogram. The demographic data, characteristics of each pregnancy and details of outcomes and management were described. Results The majority of women were Malay with mean age and body mass index of 32.9 ± 4.2 years and 27.1 ± 6.3 kg/m2 respectively. The most frequent indications for Arabin pessary insertion were previous mid-trimester miscarriage (46.4%) and early preterm birth (17.2%). A total of 73.4% of these women had the pessary inserted electively at a mean cervical length of 31.6 ± 9.1 mm at median gestation of 15.0 weeks. They were managed as outpatient (56.9%), inpatient (24.1%) or mixed (19.0%) with combination of progestogen (81.0%) and 53.4% received antenatal corticosteroids. Spontaneous preterm birth at or more than 34 weeks gestation occurred in 74.1% with birthweight at or more than 2000 g (82.4%). Despite cervical funneling in 12 women (20.7%), 66.7% delivered at or later than 34 weeks gestation and 2 (16.7%) resulted in miscarriage. Conclusions Insertion of the Arabin pessary is beneficial to prevent spontaneous preterm birth in pregnant women who are at high risk. In particular, early insertion and close monitoring allows the best possible outcomes. Trial registration This study was retrospectively registered with ClinicalTrials.gov ( NCT04638023 ) on 20/11/2020.